Finite difference method for solving fourth-order obstacle problems - Al-Said, EA; Noor, MA; Kaya, D; Al-Khaled, K (Taylor & Francis Ltd, 2004)
In this article, we introduce and develop a new finite difference method for solving a system of fourth-order boundary value problems associated with obstacle, unilateral and contact problems. The convergence analysis of the new method has been discussed and it was shown that the order is four and it gives approximations, which are better than those produced by other collocation, finite difference and spline methods. Numerical examples are presented to illustrate the applications of this method.
Keywords: finite difference method; convergence; variational inequalities; obstacle problems